2008
DOI: 10.1186/1471-2172-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic progenitor cells and interleukin-stimulated endothelium: expansion and differentiation of myeloid precursors

Abstract: Background: Cytokine-stimulated endothelial cells (EC) propagate hematopoietic progenitor cell (HPC) expansion. However, the effects on the functional capacities of cultured progenitors have not been evaluated. HPC were assessed by flow cytometry, colony and cobblestone assays and long-term cultures (LTC) after culturing in the supernatant of EC stimulated by IL-1β, IL-3 or IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…In previous studies, we demonstrated that ECs stimulated by TNF-a induced the generation of dendritic cells from CD34 1 cells for more than 6 wk [3]. ILs, on the other hand, can also induce the proliferation of hematopoietic and myeloid progenitors [4].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In previous studies, we demonstrated that ECs stimulated by TNF-a induced the generation of dendritic cells from CD34 1 cells for more than 6 wk [3]. ILs, on the other hand, can also induce the proliferation of hematopoietic and myeloid progenitors [4].…”
Section: Introductionmentioning
confidence: 84%
“…In brief, 2 Â 10 4 CD34 1 cells isolated from cord blood were cultured in 200 mL of stem cell medium [4]. Potential growth factors (all R&D, www.rndsystems.…”
Section: Quantitative Real-time Rt Pcrmentioning
confidence: 99%
See 3 more Smart Citations